Perawatan Gigi dan Kejadian Penyakit Gigi dan Mulut pada Anak Usia Sekolah di Puskesmas Jeneponto: Dental Care and the Incidence of Dental and Oral Diseases in School-Age Children at the Jeneponto Health Center - Feblina, Ayu Rahayu; Alimuddin, Hadijah; Pariati, Pariati; Alfah, Siti; Rahmadani, Nanang (Jurnal Ilmiah Amanah Akademika, 2023)
Dental and oral diseases in school children reach 60-90%. Dental care for school-age children is important to prevent dental and oral diseases. This study aims to determine the relationship between dental care efforts and the incidence of dental and oral diseases in elementary school students in the Jeneponto Community Health Center Working Area, Kec. Bontoramba. This research used a cross-sectional approach, involving 261 students selected using accidental sampling technique. Data were analyzed using the Chi-square test. The results of the analysis show a p value >0.05 for the analysis of the relationship between visiting a dentist and the incidence of dental and oral diseases; Meanwhile, the value is <0.05 for analysis of the relationship between regular tooth brushing behavior and the incidence of dental and oral diseases. Dental care by brushing teeth regularly can prevent caries, toothache and swollen teeth in school-aged children.